Relationship Between Spiritual Well-Being, Religion, and Hope Among Patients With Cancer - Neda Azimi; Elham Amanpour; Javad Khashabi; Esfandiyar Baljani (Tehran University of Medical Sciences, 2011)
Background & Aim: Spiritual well-being, religion, and hope are important factors in coping with cancer among patients. Nurses need to understand these concepts within a cultural context. This study aimed to determine the relationship between spiritual well-being, religion, and hope in patients with cancer. Methods & Materials: In this cross-sectional study, 164 patients with cancer were selected using sequential convenience sampling method. Data were collected using a four-part questionnaire. Descriptive analysis, Pearson correlation and multivariate regression analysis were used to analyses the data. Results: There were significant correlations between the existential well-being, religious well-being, and the hope. There were also significant correlations between the intrinsic religious, religious practices, and the hope. Existential well-being, organizational religiousness and intrinsic religious beliefs predicted hope. Conclusion: The results of this study emphasized on the importance of the spiritual well-being and religion as variables affecting on hope in patients with cancer. This would help nurses and clinical specialists to focus on religion and spirituality well-being in order to increase hope in the patients.